Factors Contributing to the Severity and Laterality of Pisa Syndrome in Parkinson’s Disease - Huh, Young Eun; Seo, Dae-Won; Kim, Kunhyun; Chung, Won-Ho; Kim, Seonwoo; Cho, Jin Whan (Frontiers in Aging Neuroscience, 2022)
Objective: Pisa syndrome (PS) is a disabling postural deformity in Parkinson’s disease (PD). We aimed to elucidate clinical factors determining the severity and laterality of PS in PD. Methods: In 54 PD patients with PS, we measured the clinical factors that are previously known to contribute to the occurrence of PS as follows: asymmetry of motor symptoms for the evaluation of asymmetric basal ganglia dysfunction, the degree and direction of subjective visual vertical (SVV) tilt for misperception of body verticality, canal paresis for unilateral peripheral vestibulopathy, and tonic EMG hyperactivity of paraspinal muscles for dystonia. Multivariable linear and logistic regression analyses were conducted to identify the clinical factors associated with the degree of truncal tilt, for quantification of the severity of PS, and PS tilting to the less affected side, respectively. Results: Multivariable linear regression analyses revealed larger degree of SVV tilt (beta = 0.29, standard error [SE] = 0.10, p = 0.005), right-sided SVV tilt (beta = 2.32, [SE] = 0.82, p = 0.007), and higher Hoehn and Yahr (HY) stage (beta = 4.01, SE = 1.29, p = 0.003) significantly increased the severity of PS. In multivariable logistic regression analyses, greater asymmetry of motor symptoms (odd ratio [OR] = 2.01, 95% confidence interval [CI] = 1.34-3.49) was significantly associated with PS tilting to the less affected side, while right-sided SVV tilt (OR = 0.02, 95% CI = 0.001-0.21), unilateral canal paresis (OR = 0.06, 95% CI = 0.003-0.79), and higher HY stage (OR = 0.04, 95% CI = 0.002-0.46) were associated with PS tilting to the more affected side. Conclusion: Misperception of verticality, asymmetric basal ganglia dysfunction, unilateral peripheral vestibulopathy, and motor disability are clinical factors associated with the severity and laterality of PS in PD patients.